Green and resilient: Strategies for next-generation infrastructure - Munirwan, Reza Pahlevi; Putra Jaya, Ramadhansyah; Aizat, Mohd Taib (Popular Scientist, 2025)
We are pleased to announce the second edition of the Disasters in Civil Engineering and Architecture journal. The pursuit of sustainable and resilient infrastructure continues to be a key focus in the fields of civil engineering and architecture. The second volume features recent studies that explore innovative and eco-friendly approaches in pavement and geotechnical engineering, address structural challenges, tsunami disaster and provide insights into seismic analysis.